Manganese overload as a co-factor of neurological symptoms in a patient with sclerosing cholangitis due to Langerhans cell histiocytosis - Jerome Razanamahery; Ahmed Idbaih; Matthias Papo; Fabien Robelin; Jean-Francois Emile; Sylvain Audia; Bernard Bonnotte; Julien Haroche (Haematologica)
Not available.